2000
DOI: 10.1021/jf000543s
|View full text |Cite
|
Sign up to set email alerts
|

Effect of γ-Irradiation on Phenylalanine Ammonia-lyase Activity, Total Phenolic Content, and Respiration of Mushrooms (Agaricus bisporus)

Abstract: Ionizing treatments were applied at 0.5 kGy, 1.5 kGy, and 2.5 kGy to edible mature mushrooms (Agaricus bisporus, albidus) in order to assess the effect of the gamma-irradiation on some biochemical parameters. Irradiation at doses of 1.5 kGy and 2.5 kGy reduced significantly (p < or = 0.05) the rate of respiration of the mushrooms, compared to that of samples irradiated at 0.5 kGy and nonirradiated control samples (C). Ionizing treatments increased significantly (p < or = 0.05) the phenylalanine ammonia-lyase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 20 publications
6
43
0
3
Order By: Relevance
“…This difference in trends could explain why LD of sprung fruit increased less than it did in hard and rubbery fruit in the first 5 days in Chapter 3. Similar effects of γ-irradiation of increased PPO activity have been reported in relation to browning of bananas (Thomas and Nair, 1971) and of mushroom (Benoit et al, 2000). Irradiation had higher POD activity on days 8 and 12, which was consistent with higher LD on irradiated fruit than on non-irradiated fruit.…”
Section: Discussionsupporting
confidence: 82%
“…This difference in trends could explain why LD of sprung fruit increased less than it did in hard and rubbery fruit in the first 5 days in Chapter 3. Similar effects of γ-irradiation of increased PPO activity have been reported in relation to browning of bananas (Thomas and Nair, 1971) and of mushroom (Benoit et al, 2000). Irradiation had higher POD activity on days 8 and 12, which was consistent with higher LD on irradiated fruit than on non-irradiated fruit.…”
Section: Discussionsupporting
confidence: 82%
“…During storage period, respiration rate and senescence of fresh fruits increase, as result the moisture content of fruits gradually decreases which may cause physiological loss in weight (Ayranci and Tunc, 2003). It is also reported that respiration rate often decreases with irradiation treatment may arguably due to reduced metabolic activities of irradiated fruits (Benoit et al, 2000;Boynton et al, 2005).…”
Section: Physiological Loss In Weightmentioning
confidence: 99%
“…Gamma irradiation, also, prevents the enzymatic browning of mushrooms by inactivating polyphenol oxidase, although phenylalanine ammonia-lyase increases, and as a result, the total phenolic content significantly increases (Benoit et al 2000). Irradiated mushrooms had equal or superior flavour and texture, but were somewhat discoloured (Kwon et al 1990).…”
Section: Irradiationmentioning
confidence: 99%